BMP Signaling and the Maintenance of Primordial Germ Cell Identity in Drosophila Embryos - Deshpande, Girish; Willis, Elinor; Chatterjee, Sandip; Fernandez, Robert; Dias, Kristen; Schedl, Paul (PloS one, 2014)
The specification of primordial germ cells (PGCs) and subsequent maintenance of germ-line identity in Drosophila embryos has long been thought to occur solely under the control of cell-autonomous factors deposited in the posterior pole plasm during oogenesis. However, here we document a novel role for somatic BMP signaling in the maintenance of PGC fate during the period leading up to embryonic gonad coalescence. We find that PGCs fail to maintain their germline identity when BMP signaling is compromised. They initiate but are unable to properly assemble the germline stem cell-specific organelle, the spectrosome, and they lose expression of the germline-specific gene Vasa. BMP signaling must, however, be finely tuned as there are deleterious consequences to PGCs when the pathway is excessively active. We show that one mechanism used to calibrate the effects of BMP signals is dependent on the Ubc9 homolog Lesswright (Lwr).